2007
DOI: 10.1007/s11947-007-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Formation in Foods during Thermal Processing with a Focus on Frying

Abstract: This paper summarizes the current state of knowledge on acrylamide formation in foods during thermal processing. The main pathway of acrylamide formation in foods is linked to the Maillard reaction, and in particular, the amino acid asparagine. Effects of several factors related to food composition and processing conditions on the formation levels of acrylamide, and also, other quality characteristics in thermally processed foods are discussed in detail. From a process control point of view, it is also address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 48 publications
(65 reference statements)
2
61
0
Order By: Relevance
“…The inhibition ratios were found to be 63. 65%, 74.13%, and 73.67% at 150, 200, and 250°C, respectively. Acrylamide formation in foods obeys a typical kinetic pattern during heating (Gökmen and Palazoğlu 2008). The initial period of baking is characterized by rapid loss of moisture, but the water activity is usually higher than 0.4 in this period (Gökmen et al 2007a;.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition ratios were found to be 63. 65%, 74.13%, and 73.67% at 150, 200, and 250°C, respectively. Acrylamide formation in foods obeys a typical kinetic pattern during heating (Gökmen and Palazoğlu 2008). The initial period of baking is characterized by rapid loss of moisture, but the water activity is usually higher than 0.4 in this period (Gökmen et al 2007a;.…”
Section: Resultsmentioning
confidence: 99%
“…A high temperature in the crust (N140°C) leads to intense Maillard reaction and in higher acrylamide content. It was demonstrated that acrylamide formation was concentrated at the surface layer (Acar & Gokmen 2009, Gokmen & Palazoglu 2008, Surdyk, Rosen, Andersson, & Aman 2004. Since Plantain is consumed at different stages of maturity and knowing that its moisture content increases during ripening (35-70%) a large range of water activity is to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Potato chips had especially high acrylamide contents (Rosén and Hellenäs, 2002;Tareke et al, 2002), raising a worldwide food safety concern that has resulted in lawsuits against major potato and fast food companies (http://ag.ca.gov/newsalerts/release.php?id=1207). Reducing sugars and Asn are the two major substrates for acrylamide formation in processed potato products (Goekmen and Palazoglu, 2008). Developing methods to reduce acrylamide in fried potato products has become an urgent requirement for the potato processing industry.…”
mentioning
confidence: 99%